The Development and Application of the RAND Program Classification Tool The RAND Toolkit, Volume 1 - Acosta, Joie D. (RAND Corporation, 2014)
The RAND Program Classification Tool is an instrument containing questions and response options across eight key domains that allows for the consistent description of programs in the same content area. Such data can help program portfolio managers compare programs, avoid duplication, and target technical assistance. Developed for psychological health and traumatic brain injury programs, the tool has broader applicability to other content areas.